Physically Large Displays Improve Performance on Spatial Tasks - Tan, Desney; Gergle, Darren; Scupelli, Peter; Pausch, Randy (ACM Transactions on Computer-Human Interaction, 2006)
Large wall-sized displays are becoming prevalent. Although researchers have articulated qualitative benefits of group work on large displays, little work has been done to quantify the benefits for individual users. In this article we present four experiments comparing the performance of users working on a large projected wall display to that of users working on a standard desktop monitor. In these experiments, we held the visual angle constant by adjusting the viewing distance to each of the displays. Results from the first two experiments suggest that physically large displays, even when viewed at identical visual angles as smaller ones, help users perform better on mental rotation tasks. We show through the experiments how these results may be attributed, at least in part, to large displays immersing users within the problem space and biasing them into using more efficient cognitive strategies. In the latter two experiments, we extend these results, showing the presence of these effects with more complex tasks, such as 3D navigation and mental map formation and memory. Results further show that the effects of physical display size are independent of other factors that may induce immersion, such as interactivity and mental aids within the virtual environments. We conclude with a general discussion of the findings and possibilities for future work.